Artificial intelligence and computer technologies in economics and management - Melieva Nargiza Eshboevna (THE INNOVATION ECONOMY, 2026)
article presents the results of research on the specific features of the impact of artificial intelligence technology on changing business process management systems, making management decisions, and improving the management of organizations in all sectors of the economy. The factors that led to the development of artificial intelligence technologies in modern economics and management are identified. The main areas of influence of artificial intelligence technology on the management of organizations are analyzed.